Smart Card Based Password Authenticated Key Agreement in Distributed Systems - Yadav, Pritaj; Sinha, Sitesh Kumar; Veenadhari, S (International Journal of Computer Sciences and Engineering, 2019)
The distributed system protocol based on single password is old fascinated, nowadays security issues are important aspects for any kind or sort of system protocol. As per the security need key exchange protocol which shows better security and provide greater convenience i.e. smart card and key security password for the key exchange system protocol in data sharing distributed systems. The present study proposes a general architecture construction of smart card and key security password for the key exchange system protocol in data sharing distributed systems. The present study introduces the combinatorial method of password authentication key exchange (PAKE) without public key. This constructed architecture has additional exchange phase as compare to the scheme for the public encryption (original). As compared with the protocols used in distributed system, the proposed architecture construction shows great properties in term of security and quite better computational efficiency it means operation time is less and low cost at storage.